Tapered Metal Nanoantenna Structures for Absorption Enhancement in GaAs Thin-Film Solar Cells - Dawoud, Mina; Aboul-Dahab, M.; Zainud-Deen, S. H.; Malhat, H. A. (Journal of Advanced Research in Applied Mechanics, 2020)
This paper focuses on absorption by metal nanoantennas as a means to enhance light trapping into thin-film solar cells. It determines the optimum metal nanoantennas distribution for solar cell applications, taking into account interactions between the particles as well as including the interaction with the absorbing substrate. Tapered structure is proposed for absorption enhancement using different metal nanoantennas like gold, silver, copper and aluminium. The sizes of nanoantennas are tapered in one direction. The tapered structures are composed of an array of metal nanoantennas and the sizes are tapered using two different ways according to a tapering direction. The degree of tapering can be set by controlling a scaling element. All simulation data are obtained using finite element method. Larger than 20% increase in the absorption can be achieved.